Simply green giving : create beautiful gift wrapping, tags, and handmade treasures from everyday materials - Seo, Danny (Collins, 2006)
Danny Seo transforms gift giving into a cleverly resourceful and rewarding activity. The book showcases Danny's unique take and approach to stylish green living. and features colorful photography and step-by-step instructions for easy handmade gifts and attractive recycled wrappings, along with Danny's secret tips and how-to information on living the Simply Green way.--From publisher description.